Evidenciação de capital intelectual nas páginas web de prefeituras do Tocantins - Marques., Pollianna Barros (Universidade do Vale do Rio dos Sinos, 2017)
This research analyzes the information on intellectual capital evidenced in the web pages of the cities of Tocantins, throught desk research, starting from a research composed of items related to the components of intellectual capital: human capital, structural capital and relational capital, as well as their respective subcategories. The information was subjected to descriptive analysis and statistical tests. The results of the study are: (a) the comparison of proportions revealed that the municipality of Gurupi presented greater evidence, with 81.25%, and that Palmas evidenced 75% of intellectual capital; (b) comparing the proportion of disclosure by item, it was found that the relational capital provided a proportion of 37,31%, followed by the structural capital (30,96%) and human capital (5,68%); (c) there is a relation between environmental variables budget, net chain revenue and population and the highest level of disclosure of the cites. Finally, it is concluded that there is room for more disclosure of intellectual capital by local governments; therefore, beyond the commitment to transparency and communication with citizens, the disclosure of information could add value to the municipalities
Keywords: Capital intelectual; Evidenciação; Setor público; Intellectual capital; Disclosure; Public sector; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis